Autism‐relevant traits interact with temporoparietal junction stimulation effects on social cognition: a high‐definition transcranial direct current stimulation and electroencephalography study. (27th September 2017) - Donaldson, Peter H.; Kirkovski, Melissa; Rinehart, Nicole J.; Enticott, Peter G.
Abstract: The temporoparietal junction (TPJ) is implicated in mental and emotional state attribution, processes associated with autism‐relevant traits. Transcranial direct current stimulation (tDCS) to the TPJ can influence social‐cognitive performance. However, associations with electrophysiology and autism‐relevant traits remain relatively unexamined. This study had two aims: first, exploring links between Autism‐Spectrum Quotient (AQ) scores and social‐cognitive performance; second, examining interactions between AQ scores and high‐definition‐tDCS (HD‐tDCS) applied to the right TPJ in terms of mental/emotional state attribution and neurophysiological outcomes. Fifty‐three participants completed mental/emotional state attribution tasks before and after HD‐tDCS. Pre‐stimulation mental state attribution accuracy was reduced in participants with higher AQ Switching scores. Cathodal stimulation was associated with reduced emotion attribution performance in participants with higher AQ Switching and AQ Social scores (the latter at trend‐level). Anodal stimulation more frequently interacted with AQ Social scores in terms of neurophysiology, in particular regarding reduced delta power in the left compared to right TPJ, and trend‐level positive interactions with P100 and P300 latencies during the emotion recognition task. Elements of attention/switching (AQ Switching) may subserve or underpin elements of social cognition (AQ Social), and cathodal and anodal stimulation may have differing effects depending on trait levels in these domains. This study makes an important and original contribution in terms of increasing understanding of how such trait‐level variation might interact with the effects of tDCS and also extending previous studies with regard to understanding potential roles of the rTPJ in both attention and social cognition and how autism‐relevant traits might influence TPJ function. Abstract : This study examines links between Autism‐Spectrum Quotient (AQ) scores and social cognition, and interactions between AQ and rTPJ high‐definition‐tDCS. Cathodal tDCS reduced emotion attribution performance in participants with higher AQ Switching and AQ Social scores. Anodal tDCS interacted with AQ Social scores, in particular regarding reduced delta power in the lTPJ compared to rTPJ, and trend‐level positive interactions with P100 and P300 latencies during emotion attribution. Such trait‐level variations interact with tDCS effects on both behaviour and neurophysiology.